Celiac Disease in Children with Short Stature (Incidence and Morphometric Study) (Medico Legal Update, 2020)
A study was aimed to determine the incidence of celiac disease (CD) and to make morphometric analysis of duodenal biopsy in children already diagnosed as a short stature in Mosul city. One hundred and seventy seven children aged between 3-17 years with short stature were examined. Their age, gender, serum antitransglutaminase antibody; and small intestinal biopsy were taken. The changes in the biopsy were evaluated and graded by by Corazza and Villanacci grading system. Short stature children serologically positive for celiac disease were only subjected to small intestinal biopsy. Results revealed that most predominate age group were those between 11-17 years (mean 11.8 years), with a higher male gender (107/177, 60.4%0 than female (70/177, 39.6%). Of these CD represents in 54 out of 177 children, with a grade B (b) was the predominant one (24 out from 54)(44.5%). In conclusion, short stature can be the only symptom for celiac disease in children aged between 7-11 years with higher tendency in male than female. The health significance of short stature is to subject children to intestinal biopsy for celiac disease confirmation.